Efficiency of cell-type specific and generic promoters in transducing oxytocin neurons and monitoring their neural activity during lactation - Keerthi Thirtamara Rajamani (Nature Portfolio, 2021)
Abstract Hypothalamic oxytocin (OXT) and arginine-vasopressin (AVP) neurons have been at the center of several physiological and behavioral studies. Advances in viral vector biology and the development of transgenic rodent models have allowed for targeted gene expression to study the functions of specific cell populations and brain circuits. In this study, we compared the efficiency of various adeno-associated viral vectors in these cell populations and demonstrated that none of the widely used promoters were, on their own, effective at driving expression of a down-stream fluorescent protein in OXT or AVP neurons. As anticipated, the OXT promoter could efficiently drive gene expression in OXT neurons and this efficiency is solely attributed to the promoter and not the viral serotype. We also report that a dual virus approach using an OXT promoter driven Cre recombinase significantly improved the efficiency of viral transduction in OXT neurons. Finally, we demonstrate the utility of the OXT promoter for conducting functional studies on OXT neurons by using an OXT specific viral system to record neural activity of OXT neurons in lactating female rats across time. We conclude that extreme caution is needed when employing non-neuron-specific viral approaches/promoters to study neural populations within the paraventricular nucleus of the hypothalamus.